The impact of work-family conflict on job satisfaction in teachers: a conceptual framework - Dong, Zixuan; Abd Aziz, Mohd Faiq (Macrothink Institute, 2022)
Work-family conflict has been shown to be associated with employee’s job satisfaction. However, there is little research regarding the potential mechanisms of this relationship as well as in education field. In this study, we examined the effect of work-family conflict on job satisfaction in teachers, and whether this effect is mediated by burnout and moderated by professional identity.